Forms and Functions of Foreign Language Centres in Indonesian Higher Education Institutions - Kaslan, Iswandany; Karim, Sayit Abdul; Dwiyana Putra, I Dewa Gede Rat (JOLLT Journal of Languages and Language Teaching, 2025)
This research investigates language centres within Indonesia’s higher education institutions, aiming to examine their forms, functions, and the challenges they face. Drawing on responses from 109 participants across 14 universities, the study highlights the legal basis of their establishment, with most centres relying on rector-issued regulations. The management structure emphasizes the central role of the Head of Language Centre, responsible for both administrative coordination and academic leadership. Findings reveal a broad range of language services, with Indonesian and English as core languages, supported by various regional and international languages. Educational functions feature prominently, including language training and certification. Language centres also contribute to research by managing language-related data and serve as key hubs for community service, extending their impact beyond the university setting. However, several challenges persist, including limited infrastructure and funding, repetitive programming, and human resource limitations. Future research should expand institutional coverage, apply diverse methodologies, and examine the influence of technological developments. To strengthen the strategic role of language centres, policymakers are encouraged to implement a standardized classification and accreditation system based on their varied forms and functions. Such a framework would promote quality assurance, institutional accountability, and allow universities to leverage accredited centres for academic advancement and eligibility for government-existing research grant schemes.